Grf10 regulates the response to copper, iron, and phosphate in Candida albicans - Tanaporn Wangsanut; Sylvia J Y Arnold; Safia Z Jilani; Sarah Marzec; Robert C Monsour; Ronda J Rolfes (G3: Genes, Genomes, Genetics, 2023)

(untitled)
AbstractThe pathogenic yeast, Candida albicansgrf10grf10C. albicans